2020
DOI: 10.21203/rs.3.rs-18880/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The profile of hematinic deficiencies in patients with oral lichen planus: a case-control study

Abstract: Background: Oral lichen planus (OLP) is a relatively common mucocutaneous disorder, and its causative factors and pathogenesis are not fully understood. Existing studies on the association between hematinic deficiencies and OLP are limited and inconsistent. The aim of this study was to assess the hematinic deficiencies in a cohort of OLP patients and evaluate the correlation between hematinic deficiencies and OLP.Methods: A total of 236 OLP patients and 226 age-and-gender-matched healthy controls were enrolled… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Due to the rapid renewal, the oral mucosal cells are susceptible to the effects of DNA synthesis disorders related to VB12 de ciency, and oral damage predates neurological symptoms [9,10,11]. Recently, some studies reported signi cant VB12 de ciency among symptomatic oral lichen planus patients [12]. It is challenging for oral medicine specialists to make an early diagnosis for VB12 de ciency.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid renewal, the oral mucosal cells are susceptible to the effects of DNA synthesis disorders related to VB12 de ciency, and oral damage predates neurological symptoms [9,10,11]. Recently, some studies reported signi cant VB12 de ciency among symptomatic oral lichen planus patients [12]. It is challenging for oral medicine specialists to make an early diagnosis for VB12 de ciency.…”
Section: Introductionmentioning
confidence: 99%